An Adaptive Modal Discontinuous Galerkin Finite Element Parallel Method Using Unsplit Multi-Axial Perfectly Matched Layer for Seismic Wave Modeling (Communications in Computational Physics, 2022)
The discontinuous Galerkin finite element method (DG-FEM) is a high-precision numerical simulation method widely used in various disciplines. In this paper, we derive the auxiliary ordinary differential equation complex frequency-shiftedmulti-axial perfectly matched layer (AODE CFS-MPML) in an unsplit format and combine it with any high-order adaptive DG-FEM based on an unstructured mesh to simulate seismic wave propagation. To improve the computational efficiency, we implementMessage Passing Interface (MPI) parallelization for the simulation. Comparisons ofthe numerical simulation results with the analytical solutions verify the accuracy andeffectiveness of our method. The results of numerical experiments also confirm thestability and effectiveness of the AODE CFS-MPML.
Keywords: Multi-axial PML; adaptive; parallel computing; computational seismology.